Towards Transparency in the Selection, Appraisal, and Application of Health State Utility Values in Decision-Making - Zoratti, Michael (My University, 2021)
The identification and selection of health utility inputs for health economic models is an essential yet often overlooked task in the development of useful, context-relevant models. This doctoral thesis was designed to explore existing methodologies and propose novel approaches to improve the comprehensiveness, relevance, and transparency of these processes. A broadly scoped systematic literature review was designed to identify published health utility estimates in the field of oncology. The objective of this work is to support both researchers and, importantly, reviewers who may not have sufficient resources available to evaluate the available literature and determine whether other viable inputs may have been suitable to inform a model parameter. This review infrastructure will gradually be expanded across the clinical spectrum. To evaluate the current framing of health utility-relevant concepts in critical appraisal and reporting checklists, a methods-focused literature review was conducted. While several health economic evaluation- and health utility-relevant tools and checklists were identified, this review confirmed that none were designed for the express purpose of systematically critically appraising health utility studies or evaluating context relevance. Finally, the Health utility Application Tool (HAT) was developed based on the learnings from previous research activities and engagement with knowledge users and doers in the field of health technology assessment. This tool is intended to guide researchers in selecting the most relevant evidence for models, with several questions directed toward clinical and jurisdiction-specific context. Framed primarily as a communication tool, the HAT is intended for researchers to use to document reasoning rather than for critically appraising others’ work. This body of research has established the groundwork upon which further developments may emerge. The success of these efforts will be realized over time and necessitates a commitment to knowledge translation and dissemination with sustained engagement across the research community.